Histomorphological changes, sperm quality and testosterone level after administration and cessation of Pegagan (Centella asiatica) extract in rats - Solihati, N.; Purwantara, B.; Supriatna, I.; Winarto, A. (Diponegoro University, 2018)
The objective of this study was to determine histomorphological change of seminiferous tubules, sperm quality and testosterone level after administration and cessation of pegagan extract. The research used 4x2 factorial complete randomized design, the first factor was dose-administration duration and the second factor was cessation length of pegagan extract. Parameters consisted of degree of spermatogenesis, sperm quality (motility, concentration and abnormality), and testosterone level. The data were processed using analysis of variance and Duncan’s test. Results showed that there was no interaction between dose-administration duration and cessation length. There was no significant difference of dose-administration duration of pegagan on degrees of spermatogenesis, sperm motility and testosterone level. Cessation length did not significantly affect degrees of spermatogenesis, sperm motility, and testosterone level although these results indicated that cessation of pegagan extract for 12 days increased degrees of spermatogenesis and sperm motility, indicated the antifertility potency of pegagan extract. In conclusion, Pegagan extract has potency as anti-fertility agent although the degree of spermatogenesis, sperm quality and testosterone levels were still in the normal range for the reproductive process and not irreversible, and pegagan could be explored as an reversible anti-fertility agent.